A randomized, placebo-controlled trial of online cognitive behavioral therapy for chronic insomnia disorder delivered via an automated media-rich web application. - Espie, C; Kyle, S; Williams, C; Ong, J; Douglas, N; Hames, P; Brown, J (2012)
STUDY OBJECTIVES: The internet provides a pervasive milieu for healthcare delivery. The purpose of this study was to determine the effectiveness of a novel web-based cognitive behavioral therapy (CBT) course delivered by an automated virtual therapist, when compared with a credible placebo; an approach required because web products may be intrinsically engaging, and vulnerable to placebo response. DESIGN: Randomized, placebo-controlled trial comprising 3 arms: CBT, imagery relief therapy (IRT: placebo), treatment as usual (TAU). SETTING: Online community of participants in the UK. PARTICIPANTS: One hundred sixty-four adults (120 F: [mean age 49y (18-78y)] meeting proposed DSM-5 criteria for Insomnia Disorder, randomly assigned to CBT (n = 55; 40 F), IRT placebo (n = 55; 42 F) or TAU (n = 54; 38 F). INTERVENTIONS: CBT and IRT each comprised 6 online sessions delivered by an animated personal therapist, with automated web and email support. Participants also had access to a video library/back catalogue of session content and Wikipedia style articles. Online CBT users had access to a moderated social network/community of users. TAU comprised no restrictions on usual care and access to an online sleep diary. MEASUREMENTS AND RESULTS: Major assessments at baseline, post-treatment, and at follow-up 8-weeks post-treatment; outcomes appraised by online sleep diaries and clinical status. On the primary endpoint of sleep efficiency (SE; total time asleep expressed as a percentage of the total time spent in bed), online CBT was associated with sustained improvement at post-treatment (+20%) relative to both TAU (+6%; d = 0.95) and IRT (+6%: d = 1.06), and at 8 weeks (+20%) relative to IRT (+7%: d = 1.00) and TAU (+9%: d = 0.69) These findings were mirrored across a range of sleep diary measures. Clinical benefits of CBT were evidenced by modest superiority over placebo on daytime outcomes (d = 0.23-0.37) and by substantial improved sleep-wake functioning on the Sleep Condition Indicator (range of d = 0.77-1.20). Three-quarters of CBT participants (76% [CBT] vs. 29% [IRT] and 18% [TAU]) completed treatment with SE > 80%, more than half (55% [CBT] vs. 17% [IRT] and 8% [TAU]) with SE > 85%, and over one-third (38% [CBT] vs. 6% [IRT] and 0% [TAU]) with SE > 90%; these improvements were largely maintained during follow-up. CONCLUSION: CBT delivered using a media-rich web application with automated support and a community forum is effective in improving the sleep and associated daytime functioning of adults with insomnia disorder. CLINICAL TRIAL REGISTRATION: ISRCTN - 44615689.